2019
DOI: 10.1097/md.0000000000017329
|View full text |Cite
|
Sign up to set email alerts
|

Frozen embryo transfer at the cleavage stage can be performed within the first menstrual cycle following the freeze-all strategy without adversely affecting the live birth rate

Abstract: Thus far, all clinical trials evaluating the efficacy of embryo transfer strategies have selectively delayed the first frozen embryo transfer (FET) by at least 1 menstrual cycle. Nevertheless, this approach, which is based solely on clinical experience, may create unnecessary psychological stress on infertile patients who are anxious to conceive as soon as possible. This study aimed to investigate whether the time interval between oocyte retrieval and subsequent FET affects reproductive outcomes.We implemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…As we can see in Table 1, the 12 studies included a total of 18 127 FET cycles (5457 immediate and 12 570 delayed) carried out in women from centers in 6 different countries (Belgium, Spain, Australia, China, Israel, USA, and Turkey). Ten of the publications reported single‐center studies, 9,19‐27 while one was based on a multisite IVF clinic 18 and one 12 included two centers.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As we can see in Table 1, the 12 studies included a total of 18 127 FET cycles (5457 immediate and 12 570 delayed) carried out in women from centers in 6 different countries (Belgium, Spain, Australia, China, Israel, USA, and Turkey). Ten of the publications reported single‐center studies, 9,19‐27 while one was based on a multisite IVF clinic 18 and one 12 included two centers.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies reported an upper limit of age in the inclusion criteria: >38 years, 22 >40 years, 23,24 >42 years, 25 and >45 years 9,27 . Four reported a lower limit: <18 years 9,23 and <20 years 22,24 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations